Gene regulatory networks and their applications: understanding biological and medical problems in terms of networks - Emmert-Streib, Frank; Dehmer, Matthias; Haibe-Kains, Benjamin (Frontiers in Cell and Developmental Biology, 2014)
In recent years gene regulatory networks (GRNs) have attracted a lot of interest and many methods have been introduced for their statistical inference from gene expression data. However, despite their popularity, GRNs are widely misunderstood. For this reason, we provide in this paper a general discussion and perspective of gene regulatory networks. Specifically, we discuss their meaning, the consistency among different network inference methods, ensemble methods, the assessment of GRNs, the estimated number of existing GRNs and their usage in different application domains. Furthermore, we discuss open questions and necessary steps in order to utilize gene regulatory networks in a clinical context and for personalized medicine.